Meat Quality and Carcass Characteristics of Merino Precoce Suckling Lambs Raised Under Confinement in the Mediterranean Semi-Humid Dryland of Central Chile [Calidad de Carne y Características de la Canal de Corderos Lechales Merino Precoz Criados en Confinamiento en la Zona Mediterránea Semi-Húmeda del Secano Costero Central de Chile] - Tomic-Stefanin, G (Pontificia Universidad Catolica de Chile, Facultad de Agronomia e Ingenieria Forestal, 2012)
Twenty-eight Merino Precoce suckling lambs raised under confinement in the Mediterranean semi-humid dryland of Central Chile were studied to evaluate meat quality and major carcass characteristics. Animals were grouped by slaughter weight (10 and 15 kg) and sex (7 males and 7 females in each weight group). The average commercial and true dressing percentages were 53 and 55%, the average ribeye area was 11.7 cm2, and the average dorsal fat thickness was 1.5 mm. The largest retail yields were those of the leg and shoulder, at 38 and 22%, respectively. The tissue composition of the leg was 58% muscle, 23% bone, 12% fat, 3.6% residues, and 3% shrink loss. The tissue composition of the shoulder was 57% muscle, 23% bone, 11% fat, 3.7% residues and 3.2% shrink loss. The average chemical composition of the fresh meat was 67% moisture, 19% protein, 13% ether extract, and 1.3% ash. Sensory panel evaluation indicated that almost all the sensory characteristics were within the ideal range, and the acceptability panel evaluation indicated that 15 kg lambs produced the most acceptable meat. Slaughter weight had the most significant effect on carcass and meat quality. These results confirm that Merino Precoce suckling lambs yield high-quality carcasses and highly acceptable meat.